2021
DOI: 10.1021/acs.jpcc.0c10508
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrogen Cluster Storage in Clathrate Hydrates via Defect-Mediated Lattice Engineering

Abstract: Can we create even more “plenty of room at the bottom” of the confined nanospaces in clathrate hydrates by tuning the complex interactions between the host water frameworks and guest molecules? Because the lattice of the clathrate hydrate is stabilized by van der Waals forces between the host and guest, irradiating the lattice of the clathrate hydrate with energetic particles is anticipated to introduce artificial defects on the host water molecules, resulting in creating a better occupation of guest molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…75,83 However photoelectrons liberated from ice by two-photon excitation at 265 nm would not possess energies higher than ∼1.4 eV 69,70 rendering THF fragmentation unlikely since its weakest bond (C–O) has a dissociation energy is ∼3.6 eV. 84 As mentioned earlier, all comparable clathrate studies including those in THF hydrates, 23,35 employing γ-rays or protons with energies in excess of 1 MeV display distinct radical spectra from those we observe. We posit that these higher energy irradiation sources are more likely to induce electron chemistry than two-photon threshold ionization due to increased recombinational escape probability, 68,85 additional electron sources from Auger emission following core-level ionization, 86 and the possibility of electron-impact ionization.…”
Section: Resultsmentioning
confidence: 46%
“…75,83 However photoelectrons liberated from ice by two-photon excitation at 265 nm would not possess energies higher than ∼1.4 eV 69,70 rendering THF fragmentation unlikely since its weakest bond (C–O) has a dissociation energy is ∼3.6 eV. 84 As mentioned earlier, all comparable clathrate studies including those in THF hydrates, 23,35 employing γ-rays or protons with energies in excess of 1 MeV display distinct radical spectra from those we observe. We posit that these higher energy irradiation sources are more likely to induce electron chemistry than two-photon threshold ionization due to increased recombinational escape probability, 68,85 additional electron sources from Auger emission following core-level ionization, 86 and the possibility of electron-impact ionization.…”
Section: Resultsmentioning
confidence: 46%
“…Since the later half of 2000s, there has been a growing interest in promoting H 2 hydrate formation. Notable H 2 hydrate promoters are tetrahydrofuran (THF), , propane (C 3 H 8 ), ethane (C 2 H 6 ), tetra- n -butyl ammonium bromide (TBAB), , tetra- n -butyl ammonium fluoride (TBAF), tetra- n -butyl ammonium chloride (TBACl), tetra- n -butyl phosphonium bromide (TBPB), dioxolane (DIOX), , tetrahydrothiophene (THT), , tetra- n -butyl ammonium hydroxide (TBAOH), methylcyclohexane (MCH), , 1,1-dimethylcyclohexane (DMCH), , methyl tert -butyl ether (MTBE), , furan, 2,5-dihydrofuran (DHF), tetrahydropyran (THP), cyclpentane (CP), epoxycyclopentane, noble gases such as argon, and a mixture of THF and dodecyl trimethylammonium chloride (DTACl) . The effects of these promoters on the hydrate formation rate and the H 2 storage capacity are shown visually in Figure a,b, respectively.…”
Section: Brief History Of H2 Hydrate Researchmentioning
confidence: 99%
“…They found that the H 2 diffusion coefficient at 270 K and 20 MPa increased by a factor of 2 upon the presence of perchloric acid . Meanwhile, Moon et al showed that using proton irradiation to create defects on hydrate structures led to an enhanced kinetics of H 2 uptake …”
Section: Promoters For H2 Hydrate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early on, clathrate hydrate drew attention as a potential replacement for conventional natural gas due to its natural gas hydrate form, which contains gas as a guest and exists in permafrost or sea floors . Recently, based on the unique physicochemical properties of clathrate hydrates, efforts have been made to utilize synthetic clathrate hydrates in various separation processes such as post- and pre-combustion CO 2 capture, H 2 storage, natural gas storage and transportation, wastewater desalination, and more. , …”
Section: Introductionmentioning
confidence: 99%